Hypotonia: A Clinical Sign, Different Etiologies - Esteireiro, Ana Sofia (2020)
Hypotonia is a nonspecific sign with many possible underlying aetiologies. The clinical history and neurological examination are vital, providing clues to a methodical and systematic investigation. It is essential to accomplish an early etiological diagnosis to implement adequate therapy (when available), establish prognosis and offer genetic counselling.  The authors present two clinical cases that reflect the diagnostic challenge in evaluating a newborn or infant with hypotonia.